Methamphetamine use and technology-mediated psychosocial interventions: A mini-review. (October 2021) - Rubenis, Adam J.; Baker, Amanda L.; Arunogiri, Shalini
Abstract: Engagement with face-to-face psychosocial interventions is often compromised in people using methamphetamine (MA), in the context of high rates of polysubstance use, mental health disorders, cognitive impairment and geographic isolation. Technology-mediated interventions offer flexible ways of engaging with treatment and are readily accessible. This mini-review evaluates evidence from eight studies for the effectiveness of telephone, mHealth (text-messaging and apps) and computer-based interventions for MA use. Two papers from one telephone counselling study showed a small improvement in MA-related outcomes, particularly for individuals in active use. However, a directive counselling style was associated with a higher likelihood of MA use during recovery for those higher in resistance to authority. Text-messaging interventions generally showed small but significant reductions in MA use in non-treatment seekers. When compared, there was no significant difference in level of MA use reduction between interactive, automated and self-monitoring text messages. Studies in other modalities (smartphone app, one trial; computer-based interventions, two trials) did not confer statistically significant reductions in MA use, though were likely impacted by app design and participant characteristics. Preliminary findings hint at the potential effectiveness of telephone counselling in aftercare and the capacity for text-messaging to reach those who are not in treatment. Given the small amount of existing literature, this review discusses the potential value of emerging interventions, the importance of adapting interventions to the characteristics of people who use MA and suggests specific directions for research in each technology modality.